Development of a Student-Centered Digital Mathematics Learning Prototype Using the ADDIE Model to Improve Conceptual Understanding - Ita Margaretta Br Tarigan (Karya Techno Solusindo, 2026)
Mathematics learning in higher education still faces challenges in the form of low student conceptual understanding due to the dominance of procedural approaches and the suboptimal use of digital technology. Furthermore, there are still gaps in the development of structured, student-centered, and integrated learning designs in the form of prototype-based digital learning systems. This research aims to develop a student-centered digital mathematics learning prototype using the ADDIE model to improve conceptual understanding. This research employed a Research and Development (R&D) method with Analysis and Design stages. The results are a learning prototype design that includes learning objectives, material structure, student-centered learning strategies, digital media, student activities, and an evaluation system. The prototype is designed to support concept visualization, learning interactions, and exploration and problem-solving activities. The results indicate that the developed prototype has the potential to systematically and interactively improve the effectiveness of mathematics learning. In conclusion, this prototype can serve as the basis for developing innovative digital mathematics learning. The novelty of this research lies in the integration of the ADDIE model with a student-centered approach in the design of a comprehensive digital learning prototype. REFERENCES Anisa Ulva Wahyuni & Hasanuddin. (2025). Teknologi Digital dalam pembelajaran Matematika: Tinjauan Bibliometrik terhadap Dampaknya pada Pemahaman Konsep Matematis Siswa. Buana Matematika : Jurnal Ilmiah Matematika Dan Pendidikan Matematika, 15(1), 41–56. https://doi.org/10.36456/buanamatematika.v15i1.10341 Cevikbas, M., Greefrath, G., & Siller, H.-S. (2023). Advantages and challenges of using digital technologies in mathematical modelling education – a descriptive systematic literature review. Frontiers in Education, 8, 1142556. https://doi.org/10.3389/feduc.2023.1142556 Fawns, T., Ross, J., Carbonel, H., Noteboom, J., Finnegan-Dehn, S., & Raver, M. (2023). Mapping and Tracing the Postdigital: Approaches and Parameters of Postdigital Research. Postdigital Science and Education, 5(3), 623–642. https://doi.org/10.1007/s42438-023-00391-y Gourlay, L., Rodríguez-Illera, J. L., Barberà, E., Bali, M., Gachago, D., Pallitt, N., Jones, C., Bayne, S., Hansen, S. B., Hrastinski, S., Jaldemark, J., Themelis, C., Pischetola, M., Dirckinck-Holmfeld, L., Matthews, A., Gulson, K. N., Lee, K., Bligh, B., Thibaut, P., … Knox, J. (2021). Networked Learning in 2021: A Community Definition. Postdigital Science and Education, 3(2), 326–369. https://doi.org/10.1007/s42438-021-00222-y Hafidz, M. A., Herlambang Cahya Pratama, Y., & Maulidya Effendi, P. (2024). Design Thinking: Pengembangan UI/UX Aplikasi Evaluasi Pembelajaran Mata Kuliah Berbasis Web. Jurnal Informatika Polinema, 10(3), 413–420. https://doi.org/10.33795/jip.v10i3.5176 I Gusti Agung Trisna Jayantika & Gaudensia Namur. (2022). PERAN TEKNOLOGI PEMBELAJARAN DALAM MENINGKATKAN LITERASI DIGITAL MATEMATIKA. https://doi.org/10.5281/ZENODO.7033331 Kaban, R., Sembiring, D. J., & Tarigan, I. M. B. (2023). Monitoring System for Student Internships Using the Rapid Application Development (RAD) Method. 15(02). Neef, T., Müller, S., & Mechtcherine, V. (2024). Integrating continuous mineral-impregnated carbon fibers into digital fabrication with concrete. Materials & Design, 239, 112794. https://doi.org/10.1016/j.matdes.2024.112794 Perez, A. S., Nieto-Jalil, J. M., Chim, A. I. T., Huerta, J. M. M., & Cavazos, L. L. (2025). Scientific Research Model Applied to Mathematical Modeling and Prototype Construction. 2025 IEEE Global Engineering Education Conference (EDUCON), 1–7. https://doi.org/10.1109/EDUCON62633.2025.11016324 Sa’dijah, C., Anwar, L., Hidayah, I. R., Abdullah, A. H., & Cahyowati, E. T. D. (2024). Mathematics learning models based on local wisdom of Malang to support critical and creative thinking of secondary school students. 030025. https://doi.org/10.1063/5.0234944 Salinas, P., González-Mendívil, E., Quintero, E., Ríos, H., Ramírez, H., & Morales, S. (2013). The Development of a Didactic Prototype for the Learning of Mathematics through Augmented Reality. Procedia Computer Science, 25, 62–70. https://doi.org/10.1016/j.procs.2013.11.008 Soomro, S. A., Casakin, H., & Georgiev, G. V. (2021). Sustainable Design and Prototyping Using Digital Fabrication Tools for Education. Sustainability, 13(3), 1196. https://doi.org/10.3390/su13031196 Swist, T., Gulson, K. N., & Thompson, G. (2024). Education Prototyping: A Methodological Device for Technical Democracy. Postdigital Science and Education, 6(1), 342–359. https://doi.org/10.1007/s42438-023-00426-4 Syafril, S., Asril, Z., Engkizar, E., Zafirah, A., Agusti, F. A., & Sugiharta, I. (2021). Designing prototype model of virtual geometry in mathematics learning using augmented reality. Journal of Physics: Conference Series, 1796(1), 012035. https://doi.org/10.1088/1742-6596/1796/1/012035 Tarigan, I. M. B., Tarigan, S. J. B., & Ginting, R. B. (2024). Optimalisasi Efektivitas Program MBKM: Sistem Monitoring Berbasis Lokasi dan Analisis aktivitas dengan TF-IDF. 6(1). Tarigan, I. M., Simanjorang, M. M., & Siagian, P. (2022). Analisis Kemampuan Pemecahan Masalah Matematis Siswa Ditinjau dari Perbedaan Gender di SMP N 1 Kuta Buluh. Jurnal Cendekia : Jurnal Pendidikan Matematika, 6(3), 2984–2998. https://doi.org/10.31004/cendekia.v6i3.1791 Taufikurrahman, Budiyono, & Slamet, I. (2021). Development of mathematics module based on meaningful learning. 040032. https://doi.org/10.1063/5.0043239